Cytotoxic triterpene saponins from Cercodemas anceps. Issue 16 (15th August 2015) - Cuong, Nguyen Xuan; Vien, Le Thi; Hanh, Tran Thi Hong; Thao, Nguyen Phuong; Thao, Do Thi; Thanh, Nguyen Van; Nam, Nguyen Hoai; Thung, Do Cong; Kiem, Phan Van; Minh, Chau Van
Graphical abstract: Abstract: Seven holostane-type triterpene saponins (1 –7 ), including five new compounds namely cercodemasoides A–E (2 –6 ), were isolated from the sea cucumber Cercodemas anceps . Their structures were elucidated on the basis of spectroscopic evidence including HR ESI MS, ESI MS/MS, 1D and 2D NMR. The cytotoxic effects of isolated compounds were evaluated by SRB method on five human cancer cell lines including Hep-G2 (hepatoma cancer), KB (epidermoid carcinoma), LNCaP (prostate cancer), MCF7 (breast cancer), and SK-Mel2 (melanoma). Compounds1 –7 showed potent cytotoxicity on five tested cancer cell lines with IC50 values ranging from 0.03 ± 0.01 to 7.36 ± 0.46 μM. With respect to the potent cytotoxicity of the isolated saponins, further studies are required to confirm efficacy in vivo and the mechanism of cytotoxic effects.